PERBANDINGAN IMBAL HASIL SUKUK MUDHARABAH DAN OBLIGASI KONVENSIONAL (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2014) - Balqis, Cut Aja Ratu; Fitri, Meutia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This study is aimed to observe the difference return between Mudharabah Islamic bonds and conventional bonds based on the nominal yield, current yield and yield to maturity ratio. Tests were carried out using a homogeneity of variance test (F-test) and t-test analysis. From the results of statistical analysis using t-test with a significant level of 5%, it can be concluded that there is no significant performance difference between Mudharabah Islamic bonds and conventional bonds. Then based on the average value of the variable calculation on return of bonds, the result indicate that Mudharabah has a better return than conventional bonds. Mudarabah Islamic bonds provides an average income for yield of 96% where as the conventional bonds were only able to provide an average fee of 90%. Mudharabah Islamic bond also has a better current yield by 17% compared to the conventional bonds mounting to12%. On the other hand, the average of yield to maturity rate of Mudarabah Islamic bonds was at 17% and the average of yield to maturity rate of conventional bonds was at 11%.